2018
DOI: 10.3892/or.2018.6690
|View full text |Cite
|
Sign up to set email alerts
|

hsa‑miR‑24 suppresses metastasis in nasopharyngeal carcinoma by regulating the c‑Myc/epithelial‑mesenchymal transition axis

Abstract: Distant metastasis is the major contributor to treatment failure and mortality in patients with nasopharyngeal carcinoma (NPC). The lack of effective treatment strategies for metastatic NPC is the major cause for the low survival rate. Therefore, it is crucial to understand the molecular mechanisms underlying NPC metastasis and to identify potential biomarkers for targeted therapy. MicroRNA (miRNAs or miRs) have been shown to play an important role in tumorigenesis and metastasis. In the present study, we aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The overall sample size is 1518 patients coming from 25 to 247 which from 4 countries. Among these studies, several types of cancer include lung cancer ( n =3) [ 33–35 ], hepatocellular carcinoma ( n =2) [ 36 , 37 ], colorectal cancer ( n =2) [ 29 , 38 ], nasopharyngeal carcinoma ( n =2) [ 39 , 40 ], osteosarcoma ( n =1) [ 41 ], ALL ( n =1) [ 42 ], AML ( n =1) [ 42 ], advanced gastric cancer ( n =1) [ 28 ], esophageal cancer ( n =1) [ 43 ], and head and neck squamous cell carcinoma ( n =1) [ 44 ]. As for OS, RFS, and DFS, there were seven studies directly provide HRs and its 95% CI [ 28 , 29 , 35–39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The overall sample size is 1518 patients coming from 25 to 247 which from 4 countries. Among these studies, several types of cancer include lung cancer ( n =3) [ 33–35 ], hepatocellular carcinoma ( n =2) [ 36 , 37 ], colorectal cancer ( n =2) [ 29 , 38 ], nasopharyngeal carcinoma ( n =2) [ 39 , 40 ], osteosarcoma ( n =1) [ 41 ], ALL ( n =1) [ 42 ], AML ( n =1) [ 42 ], advanced gastric cancer ( n =1) [ 28 ], esophageal cancer ( n =1) [ 43 ], and head and neck squamous cell carcinoma ( n =1) [ 44 ]. As for OS, RFS, and DFS, there were seven studies directly provide HRs and its 95% CI [ 28 , 29 , 35–39 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among these studies, several types of cancer include lung cancer (n = 3) [33][34][35], hepatocellular carcinoma (n = 2) [36,37], colorectal cancer (n = 2) [29,38], nasopharyngeal carcinoma (n = 2) [39,40], osteosarcoma (n = 1) [41], ALL (n = 1) [42], AML (n = 1) [42], advanced gastric cancer (n = 1) [28], esophageal cancer (n = 1) [43], head and neck squamous cell carcinoma (n = 1) [44]. As for OS, RFS and DFS, there were seven studies directly provide HRs and its 95% CI [28,29,[35][36][37][38][39]. In addition, the remaining eight studies only provided Kaplan-Meier curves [28,33,34,[40][41][42][43][44].…”
Section: Resultsmentioning
confidence: 99%
“…After screening the full text of these articles, 15 articles were excluded. Eventually, 15 articles published between 2012 and 2018 were included in the study [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. The study flow chart is shown in Figure 1.…”
Section: Literature Selectionmentioning
confidence: 99%
“…Studies have revealed that miR-24 involves in tumor cell proliferation, differentiation, invasion, and metastasis by regulating numerous genes, such as PTEN, TRIM11, SOX7, PRKCH, and P16 [5][6][7][8][9]. Recently, abnormal miR-24 expression has been reported to be correlated with the prognosis and clinical characteristics in tumors, including gastric cancer (GC), lung cancer (LC), colorectal cancer (CRC), acute lymphoblastic leukemia (ALL), acute myeloid leukemia (AML), hepatocellular carcinoma (HCC), nasopharyngeal carcinoma (NPC), and tongue squamous cell carcinoma (TSCC) [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Most studies reported that high miR-24 expression predicted poor prognosis, while several other studies shown the opposite view.…”
Section: Introductionmentioning
confidence: 99%